The effect of protective netting on fruit diameter, quality classification, black spotted and discoloring fruit ratios of Granny Smith Challenger - Ozturk, Ahmet; Aydın, Eren; Ozturk, Burhan; Aglar, Erdal (Journal of Postharvest Technology, 2021)
The aim of this study was to determine the effects of protective nets with different light transmittance on fruit diameter, fruit quality classification,  black spot and discoloring fruit ratios of Granny Smith Challenger apple cultivar. In the study, control, 15%, 20%, 35% and 50% shading levels  were selected as applications. In the study, in the classification made by considering the fruit diameter, the fruit were generally in the I. class,  while the lowest fruit rate was recorded in IV. class. With the shade treatment, an increase in the fruit rate of I. class and a decrease in the rate  of fruit of IV. class occurred. With 35% shade treatment, I. class fruit rate was 98% and there was no fruit in IV class with this treatment. Shade  treatment increased both the rate of extra quality fruit and the rate of cull fruit. There was an increase in black spot disease with shading and  the disease density increased in parallel with the shading level. In the study, it was determined that the shade treatment was effective on the  discoloring fruit ratio, which varies depending on the year. In both years, the highest discoloring fruit ratio was obtained with control treatment.  The rate of discoloring fruit decreased in parallel with the shading level. As a results, with this study, it was revealed that shade treatment  positively affect fruit size, quality and discoloring fruit ratio, but it increased the rate of black spot. It can be suggested that protective netting with  a shading level of 35% can be used to increase the quality of fruit.
Keywords: Malus comminus; fruit quality; fruit size; black scap